Student book based on Coastal natural resources: A development research to raise student pro-environmental character - Kasim, Yulan; Katili, Abubakar Sidik; Nusantari, Elya (Inornatus: Biology Education Journal, 2018)
The research aims to develop student books based on the potential of coastal areas to improve students' pro-environmental character. Research and development from Sugiyono was used to develop student book. as many as 10 students participated in the product trial. Two experts and one practitioner validated using a validation sheet. Measurement of pro-environmental character using pro-environmental character test. Analysis of pro-environmental characters using n-gain. The results showed that the student's book met the valid criteria (88.77%), increased the pro-environmental character of students at the medium - high level (0.33 - 0.74), and received a very good response (88% - 100%) from the students. This research concludes that the student's book based on coastal natural resources meets the valid criteria, improves the character of the environmental profile and gets a very good response. Further research to test the effectiveness needs to be done through use trials.